2012
DOI: 10.31989/ffhd.v2i4.95
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid profile of raw and locally processed seeds of Prosopis africana and Ricinus communis: potential antidotes to protein malnutrition

Abstract: Background: Increasing incidence of malnutrition occasioned by high incidence of hunger, worsening food situation in the world, insufficient availability and high cost of animal protein sources, has necessitated extensive research into and use of alternative plant protein sources especially underexploited leguminous seeds.Methods: Flours from raw, boiled and fermented seeds of Prosopis africana and Ricinus communis were evaluated for crude protein and amino acid (AA) profiles, and their protein qualities deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
(37 reference statements)
1
11
2
Order By: Relevance
“…Marangoni and Alli (1988) and Felker et al (2013) reported sulfur-containing amino acids as the limiting amino acids in pods of Prosopis species, without differencing seed from mesocarp. Thr was the limiting amino acid in seed of P. Africana (Igwe et al, 2012). Barba de la Rosa et al (2006) using a single method for aminoacid analysis, reported a good balance of essential amino acids in P. laevigata whole pod flour, with limited content of sulfurcontaining amino acids and particularly high values of Trp, an amino-acid profile that contrast with the results presented here for the same species, which could be explained by differences in the used methodology.…”
Section: Amino-acid Profilecontrasting
confidence: 53%
See 2 more Smart Citations
“…Marangoni and Alli (1988) and Felker et al (2013) reported sulfur-containing amino acids as the limiting amino acids in pods of Prosopis species, without differencing seed from mesocarp. Thr was the limiting amino acid in seed of P. Africana (Igwe et al, 2012). Barba de la Rosa et al (2006) using a single method for aminoacid analysis, reported a good balance of essential amino acids in P. laevigata whole pod flour, with limited content of sulfurcontaining amino acids and particularly high values of Trp, an amino-acid profile that contrast with the results presented here for the same species, which could be explained by differences in the used methodology.…”
Section: Amino-acid Profilecontrasting
confidence: 53%
“…The protein MF content reported here for P. laevigata (105 g/kg), is slightly higher than previous reported values for P. alba (Felker et al, 2003), P. glandulosa (Harden & Zolfaghari, 1988) and P. pallida (Felker et al, 2003) with 80, 70, and 100 g/kg, respectively. The protein content reported here for SF of P. laevigata (310 g/kg) is higher than previously reported values for P. Africana (Igwe et al, 2012) and similar to P. alba (Sciammaro et al, 2016), P. juliflora (Marangoni & Alli, 1988) and P. glandulosa (Harden & Zolfaghari, 1988). Similar whole pod flours (mesocarp-SF) protein content have been reported for P. chilensis (Astudillo et al, 2000), P. glandulosa (Harden & Zolfaghari, 1988), and P. tamarugo (Astudillo et al, 2000).…”
Section: Proximate Compositioncontrasting
confidence: 43%
See 1 more Smart Citation
“…This compares favorably with 10% desired energy requirement from proteins as noted by Wardlaw and Kessel (2002). The Leucine/IsoIeucine ratio (Table 5) of amino acid constituent of P. squarrosulus could be indication of metabolic antagonism especially with tryptophan and niacin metabolism due to low leucine content (Igwe et al, 2012). Total basic amino acids/Total acidic amino acids ratio of the studied sample is 0.33, indicating more acidic amino acids than the basic amino acids.…”
Section: Resultsmentioning
confidence: 89%
“…The less than one (˂1) value calculated for TBAA/TAAA ratio (Table 5) confirms the acidic amino acids content of C. dolichopentalum and thus could be acidic at physiological pH. This does not differ from P. Africana seeds [29,30]. TSAA showed the lowest value in amino acid groupings (Table 3).…”
Section: Page 4 Ofmentioning
confidence: 52%